2018
DOI: 10.1002/mnfr.201800510
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Administration of Lactobacillus rhamnosus HN001 Ameliorates Perinatal Broad‐Spectrum Antibiotic‐Induced Reduction in Myelopoiesis and T Cell Activation in Mouse Pups

Abstract: Postnatal administration of a single bacterial strain efficiently restores granulopoiesis and most T cell activation in neonatal mice that suffer from a perinatal antibiotic-induced compromised gut microbiota at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Exposure to oral antibiotics (ABX) can alter GM diversity and this can differ depending on the particular ABX treatment [6]. In mouse models, reduced GM diversity during bacterial or viral challenge is known to exacerbate diseases e verify [2,3,[6][7][8][13][14][15]. Modulation of GM following pre-treatment of adult mice with ABX resulted in exacerbated disease following subsequent IAV challenge, characterized by delayed virus clearance, reduced titers of virus-specific antibodies and impaired inflamma some-dependent responses by innate and adaptive immune cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to oral antibiotics (ABX) can alter GM diversity and this can differ depending on the particular ABX treatment [6]. In mouse models, reduced GM diversity during bacterial or viral challenge is known to exacerbate diseases e verify [2,3,[6][7][8][13][14][15]. Modulation of GM following pre-treatment of adult mice with ABX resulted in exacerbated disease following subsequent IAV challenge, characterized by delayed virus clearance, reduced titers of virus-specific antibodies and impaired inflamma some-dependent responses by innate and adaptive immune cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These results had good agreement with the findings of Fuglsang et al in which perinatal broad-spectrum antibiotics treatment decreased the proportions of bone marrow granulocyte-macrophage progenitor cells, mature granulocytes, spleen granulocytes and B cells in newborn mice. Furthermore, these damages induced by perinatal antibiotics administration in offspring immunity could not be restored with decreased splenic T helper cells and cytotoxic T cells in the later life[32]. On other hand, Nyangahu et al reported that oral administration of vancomycin during pregnancy and nursing not only altered the maternal immunity, as demonstrated by significantly higher levels of both total IgG and IgM in breastmilk, but also altered the immunity of pups, as demonstrated with the significant increased lymphocyte numbers and the elevated numbers of both CD4 + T cells and B cells, most notable Follicular B cells[19].…”
mentioning
confidence: 94%
“…However, the altered fecal microbial communities in our study were entirely different from other studies. Fuglsang et al reported that Cyanobacteria became the dominate phylum, but not Tenericutes, in the fecal microbiota of pregnant mice treated with a mix of ampicillin trihydrate, gentamicin sulfate and metronidazole for 7 days before delivery[32]. Nyangahu et al reported that Firmicutes became the most dominate phylum in the maternal fecal microbiota treated with vancomycin 5 days prior…”
mentioning
confidence: 99%